Skogsbrukets framtida arbetskraftsförsörjning : skogsmaskinföraryrkets attraktionskraft - Valinger, Karin (SLU/Dept. of Forest Resource Management, 2009)
The scarcity of qualified forest machine operators as well as the increased competition for competent machine operators among others from the mining industry in Norrland, were the reasons to investigate what attracts and what deters active and potential forest machine operators to the occupation. An interview study was conducted among four groups with four persons in each group. The groups were students in year 1 and 3 respectively at a forestry school at upper secondary school level as well as employees of a forest company and employees of contractors. The majority of all respondents were of the opinion that their interests in machines had been important for the choice of occupation. But for the active machine operators both the interest in the forest and their interest for machines have had importance for choosing this occupation. More students than active machine operators could consider a change of occupation. The salary level was the most important reason for those that could consider a change. An increased salary level was also the most mentioned recommendation among the respondents to increase the attraction of the occupation. The most important aspect however in work was comradeship and an interesting and varied work, something that is not offered in the present work organization according to respondents. The possibility to flexible working hours was highly appreciated by the active machine operators while at the same time the shift forms used at present were considered to be among the worst aspects of the work. Freedom in the meaning of being in charge of once own performance, working outdoors and/or flexible working hours is still an important aspect attracting machine operators to the occupation. Suggestions for improvements are to start stimulating young people's interest in the forest early. To limit the risk of losing qualified personnel, it is important to develop leadership, working conditions and salary.